Alcohol‐Induced Blackouts: A Review of Recent Clinical Research with Practical Implications and Recommendations for Future Studies. (8th April 2016) - Wetherill, Reagan R.; Fromme, Kim
Abstract : Background: Alcohol‐induced blackouts, or memory loss for all or portions of events that occurred during a drinking episode, are reported by approximately 50% of drinkers and are associated with a wide range of negative consequences, including injury and death. As such, identifying the factors that contribute to and result from alcohol‐induced blackouts is critical in developing effective prevention programs. Here, we provide an updated review (2010 to 2015) of clinical research focused on alcohol‐induced blackouts, outline practical and clinical implications, and provide recommendations for future research. Methods: A comprehensive, systematic literature review was conducted to examine all articles published between January 2010 through August 2015 that focused on vulnerabilities, consequences, and possible mechanisms for alcohol‐induced blackouts. Results: Twenty‐six studies reported on alcohol‐induced blackouts. Fifteen studies examined prevalence and/or predictors of alcohol‐induced blackouts. Six publications described the consequences of alcohol‐induced blackouts, and 5 studies explored potential cognitive and neurobiological mechanisms underlying alcohol‐induced blackouts. Conclusions: Recent research on alcohol‐induced blackouts suggests that individual differences, not just alcohol consumption, increase the likelihood of experiencing an alcohol‐induced blackout, and the consequences of alcohol‐induced blackouts extend beyond the consequences related to the drinking episode to include psychiatric symptoms and neurobiological abnormalities. Prospective studies and a standardized assessment of alcohol‐induced blackouts are needed to fully characterize factors associated with alcohol‐induced blackouts and to improve prevention strategies. Abstract : Alcohol‐induced blackouts, or memory loss for all or portions of events that occurred during a drinking episode, are reported by approximately 50% of drinkers and are associated with a wide range of negative consequences. Here, we provide an updated review (2010 to 2015) of clinical research focused on alcohol‐induced blackouts, discuss potential neurobiological mechanisms, outline practical and clinical implications, and provide recommendations for future research.